HUBUNGAN ANTARA DIABETES MELITUS TIPE 2 DENGAN DESTRUKSI PERIODONTAL PADA PENDERITA PERIODONTITIS: RELATION OF TYPE TWO DIABETES WITH PERIODONTAL DESTRUCTION IN PATIENT WITH PERIODONTITIS - Pitu Wulandari; Ulipe (TALENTA, 2010)
Type 2 diabetes mellitus (T2DM) is one of the most common diseases found in the world especially in Indonesia. This disease has many oral manifestations and one of them is periodontitis. The aim of this study was to know the correlat of T2DM and periodontal destruction in those with periodontitis by using a case control study. The study comprised of two groups of subjects who had T2DM and non diabetes respectively. Samples were taken from three places in Medan. Each group was taken 45 people, so the total numbers of samples are 90 people. Periodontal destruction was measured using periodontal index by Russel, probing depth and clinical attachment loss. Data was analyzed using independent Student and Pearson correlation tests. The result showed that the periodontal index and clinical attachment loss in T2DM patients were bigger than those in controls. Conversely, the probing depth in T2DM patients was smaller than those in controls but it was not statistically significant. Beside that, the increasing of blood glucose did not influence the periodontal condition. In conclusion, there was a correlation between T2DM and periodontal destruction in those with periodontitis.